Causes of a Negative Ethanol Gelation Test in Diffuse Intravascular Coagulation - Gerrits, W. B. J; Prakke, Elisabeth M; van der Meer, J; Vreeken, J (Thrombosis and Haemostasis, 1974)
The clinical value of the ethanol gelation test (EGT) in diagnosing diffuse intravascular coagulation (DIC) has been questioned because of the occasional finding of a negative test, while other laboratory data pointed to DIC. Therefore, the behaviour of the EGT during thrombin infusions in rabbits was studied, with special reference to the fibrinogen level and activation of fibrinolysis. Fibrinolytic activity was inhibited or induced by synchronous infusion of epsilon-aminocaproic acid or plasmin respectively. The results obtained show that apart from severe depletion of fibrinogen strong activation of fibrinolysis can cause a negative EGT during thrombin infusions in rabbits. This phenomenon could not be ascribed to high levels of fibrin degradation products (fdp); it might be due to plasmin digestion of fibrin monomers. In vitro studies with human plasma confirmed that the EGT becomes negative at a fibrinogen level of less than 20 mg per 100 ml or by plasmin activity in the presence of a normal fibrinogen level.Whereas a positive EGT is highly specific for DIC, these studies show that a negative EGT does not exclude the presence of DIC.